The role of sports in forming nationalism: A study on the most significant sports event in Indonesia - Kenius Kogoya; Pawennari Hijjang; Akhmad Kadir; Tri Setyo Guntoro; Zainuddin Amali; Akbar Silo; Saharuddin Ita; Marlina Flassy; Fredrik Sokoy; Gerdha Numberi; Evi Sinaga; Rodhi Rushdianto Hidayat; et al. (Universidad de Murcia, 2024)
Nationalism is considered a significant issue due to a movement in Papua, Indonesia, which seeks to separate itself from Indonesia. However, studies regarding this issue are still limited and need to be conducted, especially related to sports. Therefore, the purpose of this study was to reveal the role of sporting events in shaping nationalism. We used the Mixed Method Research with a sequential exploratory design to understand the phenomenon of nationalism and sports in the biggest national sports event (PON). Twenty-four key informants and 365 respondents were involved in this study. Interviews, FGDs, documentation, and questionnaires were used to collect the data. Data analysis used ATLAS.ti and IBM SPSS programs. The results of the study found that the 20th PON in Papua (PON XX Papua), Indonesia, became a stimulus for the growth of nationalism among the indigenous Papuans (OAP). These sporting events also strengthened unity and togetherness and made society tolerant and open. This research proves that sporting events have eroded the sense of dual nationalism of OAP because, through sports, namely the choice of Papua as the host of the PON XX, OAP feels valued, cared for, and trusted by the State.